Associations Between Physical Activity and Hypertension in Chinese Children: A Cross-Sectional Study From Chongqing - Wang, Qianqian; Qu, Ping; Chen, Jingyu; Tang, Xian; Hao, Guang; Liang, Xiaohua (Frontiers in Medicine, 2021)
Background: Childhood blood pressure is a marker for cardiovascular disease risk later in life. Few studies examined the association between physical activity (PA) and hypertension in Chinese children, and this study aimed to explore this relationship. Methods: A cross-sectional study among pupils was conducted in Chongqing in 2014. In total, 15,203 children aged 6 to 12 years in Chongqing were included in this study. The duration of self-reported PA on school days and the weekend in pupils were collected with a standardized questionnaire. Results: The results showed that, on school days, only 22.3% of boys and 17.8% of girls engaged in more than 60 min of PA per day; while on the weekend, only 38.5% of boys and 32.0% of girls engaged in at least 60 min of PA per day. There was no strong evidence for an association between PA and systolic or diastolic hypertension in boys. However, in girls, a weak negative association between PA on weekdays and hypertension was observed, and there was a significant interactive effect of PA and obesity on hypertension risk (P for interaction = 0.042). In obese children, PA was positively related to the risk of hypertension. Conclusion: The overall level of PA among pupils in Chongqing was insufficient, and a weak negative relationship between PA and hypertension was found in girls.